The green turtle Chelonia mydas as a marine and coastal environmental sentinels: anthropogenic activities and diseases - Isabela Guarnier Domiciano (Semina: Ciências Agrárias, 2017)
The green turtle Chelonia mydas is a widely distributed, slowly maturing species with a complex life cycle, using both oceanic and coastal environments. The species is exposed to different threats and is considered an environmental sentinel that indicates variation among, and the severity of hazards to marine ecosystems. This study aimed to describe both anthropogenic impacts, and infectious and parasitic diseases in C. mydas - including cases along the Brazilian coast - and implications for conservation. Bycatch is reported as the main threat to the conservation of this species, followed by debris ingestion, collisions with boats, dredging, and chronic environmental contamination. All of these impacts may directly or indirectly cause death, by facilitating contact with pathological agents and by increasing vulnerability to secondary diseases. The pathological agents associated with lesions includ e viruses, bacteria, fungi, protozoa, and helminths. Fibropapillomatosis is an example of a chronic disease characterized by cutaneous and visceral tumors that affects mostly juvenile C. mydas worldwide and is associated with the Chelonid herpesvirus 5. The bacterias Vibrio alginolyticus , Aeromonas hydrophila , and Pseudomonas fluorescens are found in the aquatic environment and among C. mydas lesions in various organs. Trematode adults and eggs of the family Spirorchiidae are also frequent in systemic cardiovascular diseases of C. mydas . The direct impact s of anthropogenic activities and diseases are synergistic and may affect the specie’s health and conservation. Therefore, the monitoring and systematic diagnosing of diseases and causes of death - including necropsy, histopathology, and molecular exams - are necessary to assess a population’s health, to support appropriate decisions of coastal management and to target future research topics that optimize C. mydas conservation.